EVEN AND ODD FUNCTIONS (Spectrum Journal of Innovation, Reforms and Development, 2022)
This article talks about even and odd functions.A function in maths is a special relationship among the inputs (i.e. the domain) and their outputs (known as the codomain) where each input has exactly one output, and the output can be traced back to its input.